2020
DOI: 10.1111/1750-3841.15355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pinhão starch and natural extracts on the performance of thermoplastic cassava starch/PBAT extruded blown films as a technological approach for bio‐based packaging material

Abstract: Films were produced using the blown extrusion method from blends made with cassava and pinhão thermoplastic starch, compostable polyester (poly(butylene adipate co‐terephthalate, PBAT) and natural extracts (rosemary and green tea). The effect of the incorporation of the extracts and the type of starch added in the film properties were investigated following the mixture design (23) approach. Regression models and response surface curves were generated to predict the film properties. The effect of the cold stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The fourth thermal event occurred at initial temperatures of 334.06–391.09°C and DTG peaks of 385.88–390.09°C, respectively (Figure 6b), related to the thermal degradation of PBAT molecules (Cardoso et al, 2017; Müller et al, 2020). Films containing microalgae cells had a higher residual mass after the last stage of thermal degradation, contributing to more organic matter content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth thermal event occurred at initial temperatures of 334.06–391.09°C and DTG peaks of 385.88–390.09°C, respectively (Figure 6b), related to the thermal degradation of PBAT molecules (Cardoso et al, 2017; Müller et al, 2020). Films containing microalgae cells had a higher residual mass after the last stage of thermal degradation, contributing to more organic matter content.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of its mixture with biodegradable polyesters are a strategy to improve packaging materials' mechanical and barrier properties (Garcia et al, 2018). Thus, blends with poly(butylene adipate‐ co ‐terephthalate) (PBAT; Balan et al, 2021; Mücke et al, 2021; Müller et al, 2020), poly(lactic acid) (PLA) (Mangaraj et al, 2019), and poly(vinyl alcohol) (Javed et al, 2016), among others, have been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these bio molecules are prone to water transmission through films; their fragile nature and lack of mechanical stability have led to the concept of coupling with lipids or other biopolymers to counter these limitations [49]. Composite biofilms made with cassava, pinhão thermoplastic starch, compostable polyester poly butylene adipate co-terephthalate, green tea, and rosemary extracts helped improve water vapor permeability [50]. A progression in flexibility, water vapor resistance, and TS was perceived in a starch-based film reinforced with cellulose nanofibers [51].…”
Section: Starchmentioning
confidence: 99%
“…Another natural extract with the potential to be incorporated into biopolymeric films is the Araucaria angustifolia extract, as demonstrated by Da Silva et al [78], which was incorporated into films based on cassava starch and poly (butylene adipate co-terephthalate), also known as PBAT. Additionally, Muller et al [79] demonstrated that cassava starch could be replaced by A. angustifolia starch, which was extracted from its seeds. The authors also successfully incorporated rosemary and green tea aqueous extract in the films, and the extract directly influenced the physicochemical properties of the produced films.…”
Section: Packaging Applicationsmentioning
confidence: 99%